2007
DOI: 10.1007/s00125-007-0617-0
|View full text |Cite
|
Sign up to set email alerts
|

In utero undernutrition reduces diabetes incidence in non-obese diabetic mice

Abstract: Aims/hypothesis Observational studies in humans suggest that low birthweight may decrease the risk of type 1 diabetes, but the mechanism is unknown. We hypothesised that antenatal undernutrition would decrease the incidence of type 1 diabetes in non-obese diabetic (NOD) mice. Materials and methods A 40% restriction of energy intake was applied to pregnant NOD dams from day 12.5 to day 18.5 of gestation, resulting in intrauterine growth retardation of offspring. All mice were fed a standard diet after weaning. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
19
0

Year Published

2007
2007
2013
2013

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 53 publications
4
19
0
Order By: Relevance
“…Surprisingly, the incidence of b-cell apoptosis in food-restricted animals was significantly lower than in controls at all ages examined. Other authors have also reported that intrauterine malnutrition reduces the incidence of type 1 diabetes in non-obese diabetic mice altering b-cell apoptosis levels (Oge et al 2007). Apparently, in view of our results, even increased b-cell neogenesis and decreased b-cell apoptosis are insufficient to restore normal b-cell mass when proliferation and b-cell mass are already affected.…”
Section: Discussionsupporting
confidence: 57%
“…Surprisingly, the incidence of b-cell apoptosis in food-restricted animals was significantly lower than in controls at all ages examined. Other authors have also reported that intrauterine malnutrition reduces the incidence of type 1 diabetes in non-obese diabetic mice altering b-cell apoptosis levels (Oge et al 2007). Apparently, in view of our results, even increased b-cell neogenesis and decreased b-cell apoptosis are insufficient to restore normal b-cell mass when proliferation and b-cell mass are already affected.…”
Section: Discussionsupporting
confidence: 57%
“…A recent experimental study in NOD mice demonstrated that calorific restriction during pregnancy resulted in reduced birthweight, leading to reduced risk of diabetes by 24 weeks [49]. Also an observational study in BioBreeding rats demonstrated a higher risk of diabetes with increased birthweight [50].…”
Section: Discussionmentioning
confidence: 99%
“…Twenty-six studies reported on protein restriction, one using a mouse model [4], and twenty-five using a rat model . Twenty-four reported on general (caloric) undernutrition, one study using guinea pigs [30] and two on a mouse model [31,32], five using a sheep model [33][34][35][36][37] and 16 studies on rats [7,8,13,[38][39][40][41][42][43][44][45][46][47][48][49][50][51] .…”
Section: Resultsmentioning
confidence: 99%
“…Randomization was reported in twenty-four studies, either randomization to the dietary regimen or randomly selecting the pups that were studied from the litters [14,15,[17][18][19][20][21][22][23][24]26,28,29,31,32,[34][35][36]39,42,44,48,50,[52][53][54]. None of the studies reported a sample size calculation or methods for concealment of allocation.…”
Section: Methodological Aspectsmentioning
confidence: 99%
See 1 more Smart Citation